Oblikovalski vidiki urejanja prostora ob avtocestah - Gruev, Marta (Urbani izziv, 1998)
The project of highway construction is still, altought its realisation is underway, entangled in fundamental conceptual dilemmas concerning goals, criteria and parameters. The programme has wide public support, neverthless modes of implementation are subject to vast professional and public critique; public concerning expendinture, professional concerning establishing suitable criteria. The next hinderance is the (mis)understanding of the road as an object with cultural value; the consequence of such practice being in the reduction of designers into decorators of adopted decisions.
Keywords: avtoceste; krajinsko oblikovanje; obcestna krajina; obcestne površine; prostorsko urejanje; zelene površine